Composite Materials Science and Engineering - Chawla, Krishan K.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
This updated third edition of Krishan Chawla$1 (Bs widely used textbook, Composite Materials, offers integrated and completely up-to-date coverage of composite materials. The book focuses on the triad of processing, structure, and properties, while providing a well-balanced treatment of the materials science and mechanics of composites. In this edition of Composite Materials, revised and updated throughout, increasing use of composites in industry (especially aerospace and energy) and new developments in the field are highlighted. There is a new chapter on non-conventional composites, which covers polymer, metal and ceramic matrix nanocomposites, self-healing composites, self-reinforced composites, biocomposites and laminates made of metals and polymer matrix composites. The third edition also includes new solved examples and problems as well as increased coverage of: Carbon/carbon brakes Composites for civilian aircraft and jet engines Second generation high-temperature superconducting composites Composites for use in windmill blades WC/metal particulate composites Examples of practical applications in various fields are given throughout the book, and extensive references to the literature are provided. The book is intended for use in graduate and upper-division undergraduate courses, and as a reference for the practicing engineers and researchers in industry and academia.s
1. Introduction -- 2. Reinforcements -- 3. Matrix Materials -- 4. Interfaces -- 5. Polymer Matrix Composites -- 6. Metal Matrix Composites -- 7. Ceramic Matrix Composites -- 8. Carbon Fiber/Carbon Matrix Composites -- 9. Multifilamentary Superconducting Composites -- 10. Micromechanics of Composites -- 11. Macromechanics of Composites -- 12. Monotonic Strength and Fracture -- 13. Fatigue and Creep -- 14. Designing with Composites -- 15. Non-Conventional Composites.
Keywords: Polymers; Mechanical engineering; Engineering design; Civil engineering; Materials Science; Ceramics, Glass, Composites, Natural Methods; Engineering Design; Polymer Sciences; Mechanical Engineering; Civil Engineering